Best Practices for Hospital-Based Donor Care Unit Operations - Emily A. Vail, MD; Varun K. Goyal, MD; Ashley C. McGinity, MD; Todd Sarge, MD; Julie K. Heimbach, MD; Arthur R. Mielke, MD, MPH; Allison J. Tompeck, MD; Carolina B. Maciel, MD; Katharina M. Busl, MD; Thomas M. Leventhal, MD; Devang K. Sanghavi, MBBS, MD; Rishi Kumar, MD; et al. (CHEST Critical Care)
United States organ procurement organizations increasingly are centralizing the management and recovery of organs from deceased donors into dedicated donor care units (DCUs) with growing evidence of effectiveness. This paradigm shift offers logistical advantages, but introduces new considerations for intensivists responsible for the safe, effective, and efficient management of deceased potential organ donors. In this How I Do It article, intensivist leaders of 12 US DCUs collaborating in the Donor Care Unit Network for Optimizing Recovery group describe best practices for delivering care and organ recovery from deceased donors after brain death and circulatory death in hospital-based donor care units. Specific considerations include donor transfers, clinical donor management, performance assessment, and quality improvement.